(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article analyzes the technology of extracting molybdenum from technological solutions formed from uranium deposits. Molybdenum is an essential element for the metallurgical, chemical and electrical industries, and its extraction methods, including precipitation, ion exchange, extraction and electrolysis processes, are described. The efficiency, environmental and economic aspects of these processes are also discussed. Improving the technology of extracting molybdenum will contribute to efficient resource use and reduced industrial waste.